Subdiaphragmatic Vagotomy With Pyloroplasty Ameliorates the Obesity Caused by Genetic Deletion of the Melanocortin 4 Receptor in the Mouse - Dezfuli, Ghazaul; Gillis, Richard A.; Tatge, Jaclyn E.; Duncan, Kimbell R.; Dretchen, Kenneth L.; Jackson, Patrick G.; Verbalis, Joseph G.; Sahibzada, Niaz (Frontiers in Neuroscience, 2018)
ABSTRACT Background/Objectives: We tested the hypothesis that abolishing vagal nerve activity will reverse the obesity phenotype of melanocortin 4 receptor knockout mice (Mc4r -/-). Subjects/Methods: In two separate studies, we examined the efficacy of bilateral subdiaphragmatic vagotomy (SDV) with pyloroplasty in the prevention and treatment of obesity in Mc4r -/-mice. Results: In the first study, SDV prevented > 20% increase in body weight (BW) associated with this genotype. This was correlated with a transient reduction in overall food intake (FI) in the preventative arm of the study. Initially, SDV mice had reduced weekly FI; however, FI normalized to that of controls and baseline FI within the 8-week study period. In the second study, the severe obesity that is characteristic of the adult Mc4r -/- genotype was significantly improved by SDV with a magnitude of 30% loss in excess BW over a 4-week period. Consistent with the first preventative study, within the treatment arm, SDV mice also demonstrated a transient reduction in FI relative to control and baseline levels that normalized over subsequent weeks. In addition to the accompanying loss in weight, mice subjected to SDV showed a decrease in respiratory exchange ratio (RER), and an increase in locomotor activity (LA). Analysis of the white fat-pad deposits of these mice showed that they were significantly less than the control groups. Conclusions: Altogether, our data demonstrates that SDV both prevents gain in BW and causes weight loss in severely obese Mc4r -/- mice. Moreover, it suggests that an important aspect of weight reduction for this type of monogenic obesity involves loss of signaling in the efferent vagal motor neurons.